Utang Luar Negeri dan Pertumbuhan Ekonomi Indonesia - Rita Yunus; Rahmatia Rahmatia; Anas Iswanto Anwar; Sanusi Fattah (Pascasarjana STIE Amkop Makassar, 2021)
AbstrakDevelopment in Indonesia runs by making economic growth a target. The large and growing amount of foreign investment in Indonesia attests to the great dependence of the domestic economy on foreign countries. The low level of domestic savings does not allow for adequate investment, so developing country governments have to attract foreign loans and investment. This study aims to look at the theoretical relationship between foreign debt and economic growth in relation to the latest empirical economic data, as well as to see the impact and solutions to minimize foreign debt. Keywords: Foreign Debt, Growth